Rendimiento académico y relaciones interpersonales en estudiantes de ortodoncia (2020)
Introduction: Academic performance is a multifactorial concept that is difficult to understand. Qualitative approaches allow the understanding of several factors that compose it. Objective: To explore, from the perspective of orthodontic students, their experiences between academic performance and their social relationships with their peers and with their teachers. Methods: A qualitative hermeneutic study through semi-structured interviews and an analysis from the illustrative perspective of Damaziére and Dubar. Results: Peer relations were important as support mechanisms between high and low academic performance students. Relationships with teachers are highly relevant when establishing situations that lead to staying or coming out of low performance. Conclusions: Relationships between students, and between students and teachers, are important to understand the most relevants factors when thinking about academic performance in orthodontic graduate schools.